KAJIAN EFISIENSI TONASE KONSTRUKSI BAJA PREENGINEERING BUILDING PADA PROYEK STASIUN KRL DI KOTA JAKARTA - Lana Surya Adi Permana; Theresa Leony; Agung Bhakti Utama; Hendra Adi Wijaya (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
Technological advances offer new breakthroughs that are more effective and efficient, including in terms of construction methods. One of the breakthroughs is the steel construction of pre-engineering buildings. This study aims at calculating how much tonnage efficiency in steel construction pre-engineering building when compared to conventional steel construction. This research methodology starts from collecting secondary data from one of Commuter Line Station Project in Jakarta City, then modeling conventional steel construction using ETABS software. The results are analyzed by manual structural calculations. After that, quantity takeoff is undertaken towards conventional steel construction and pre-engineering building. The total tonnage for pre-engineering steel construction is 203.45 tons while the total tonnage for conventional steel construction is 346.48 tons. The efficiency of steel construction pre-engineering building is 41.25%.